2019
DOI: 10.1016/j.heliyon.2019.e02198
|View full text |Cite
|
Sign up to set email alerts
|

Non-biodegradable polymeric waste pyrolysis for energy recovery

Abstract: Nowadays, increasing population, widespread urbanization, rise in living standards together with versatile use of polymers have caused non-biodegradable polymeric wastes affecting the environment a chronic global problem, simultaneously, the existing high energy demand in our society is a matter of great concern. Hence forth, this review article provides an insight into the technological approach of pyrolysis emphasizing catalytic pyrolysis for conversion of polymeric wastes into energy products and presents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 171 publications
2
45
0
Order By: Relevance
“…The plastic wastes are bulkier than the organic residues and a large part of these wastes do not degrade. High continuous demand for plastics, causes plastic wastes to accumulate in land lls, take up a lot of space, and also environmental hazards (Dwivedi et al 2019). Mass consumption of plastic threatens the lives of not only marine animals but also humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plastic wastes are bulkier than the organic residues and a large part of these wastes do not degrade. High continuous demand for plastics, causes plastic wastes to accumulate in land lls, take up a lot of space, and also environmental hazards (Dwivedi et al 2019). Mass consumption of plastic threatens the lives of not only marine animals but also humans.…”
Section: Introductionmentioning
confidence: 99%
“…Waste plastics must be reused or recycled to protect the ecosystem (Park et al 2019). Post-use waste plastic is appropriate for recycling (Schneider et al 2017) and they can be grouped in different kinds of waste plastics such as high-density polyethylene (HDPE), low-density polyethylene (LDPE), polyethylene terephthalate (PET), polypropylene (PP), polystyrene (PS), polyamide (PA), polyvinyl-chloride (PVC) (Dwivedi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various conversion technologies, pyrolysis of plastic waste offers a practical way to produce fuel-grade bio-oil and fuel gas while simultaneously managing plastic waste in a manner that will not harm the environment [5]. Several studies have reported on the suitability of pyrolysis as a thermochemical recycling technique for plastics [6]. Valuable oil and gas products are formed from the pyrolysis of plastic waste [7].…”
Section: Introductionmentioning
confidence: 99%
“…Polymers, as materials that are used daily, contribute fundamentally in our daily waste production. Daily use in vast applications in various sectors resulted into enormously increased global production and disposal over the years [8]. Waste polymeric materials can be described as mixtures of different polymer molecules, for example high density polyethylene (HDPE), low density polyethylene (LDPE), polyethylene terephthalate (PET), polypropylene (PP), polystyrene (PS), polyamide(PA), polyvinyl-chloride(PVC), polyacrylate (PAC), etc., [9,10].…”
Section: Introductionmentioning
confidence: 99%